Collapse analysis and damage evaluation of typical simply supported double-pier RC bridge under truck collision. (October 2021) - Li, R.W.; Cao, D.S.; Wu, H.; Wang, D.F.
Abstract: Vehicular collision with bridge pier can cause significant structural damage, and even partial or full collapse of the bridge, while the existing work mainly focuses on the vehicular-impact resistance of bridge pier. This study aims to study the collapse process and damage levels of the bridge collided by medium and heavy trucks. Firstly, the refined finite element (FE) model of the typical simply supported two-span double-pier RC bridge is established via the commercial software LS-DYNA, and the adopted material constitutive models and numerical algorithms are validated by comparing with the prototype truck-pier collision test and full-scale drop-weight test on RC beam. Then, the validated FE model is employed to numerically reproduce the actual heavy truck collision accident involving the collapse of bridge, and the dynamic behaviors and collapse process of the collided bridge are analyzed. It shows that, for the present bridge type: (i) truck-bridge collision is not a single impact but a successive impact with bumper, engine and cargo, in which the shear failure on the reinforced concrete bridge pier (RCBP) induced by the engine impact is the dominant factor resulting in the bridge collapse; (ii) during the collision process, the impacted RCBP firstly suffers shear failure at the bottom, and followed by the inclination of the bent cap and superstructure, and then the neighboring RCBP sustains flexible-shear failure at the top, which eventually results in the instability of substructure and collapse of superstructure. Furthermore, a total of 35 truck-bridge collision cases are numerically simulated and assessed, and a new quantitative damage evaluation approach, including the modified damage index, damage level and evaluation criterion, is proposed for the bridge under vehicular collision. In addition, the relationship between the damage level of the collided bridge and superstructure inclination is clarified, which is beneficial for bridge engineers to feasibly assess the vehicular-impact resistance of bridge.